ANALISIS TERHADAP JAWABAN SOAL BANGUN RUANG SISI DATAR DITINJAU DARI MISTAKE DAN KEMAMPUAN PEMAHAMAN MATEMATIS - Devi Ambarwati; Usep Kosasih; Didin Wahidin (Universitas Islam Nusantara, 2022)
Polyhedron are a part of mathematics that are often considered difficult by students, so there are many mistakes made by students in solving problems of polyhedron. This is caused by the lack of students' mathematical understanding ability. Therefore, it is necessary to analyze the students' mistakes in solving mathematical understanding problems with the discussion of polyhedron. Based on this, this study aims to (1) determine the relationship between mathematical understanding and the student's mistake phenomenon (2) find out the forms of mistakes made by students in solving the problem of polyhedron. Participants in this study consisted of 7 students who were selected according to research needs. This study uses a qualitative approach and descriptive method with a case study design. The data obtained were analyzed using constant comparative techniques and qualitative coding. The results of this study indicate the forms of mistakes that arise from solving mathematical understanding ability test questions, namely (1) mistakes in identifying concepts (2) mistakes in absorbing information about questions (3) mistakes in using principles (4) mistakes in completion procedures (5) calculation mistakes on the process of determining the final answer.